Development co-operation : efforts and policies of the members of the Development Assistance Committee : 1982 review - Organisation for Economic Co-operation and Development. Development Assistance Committee (Paris Cedex : Organisation for Economic Co-operation and Development, 1982)
This annual report issued by the Development Assistance Committee. Part 1, deals on economic progress in the most disadvantaged countries. Part 2,3, and 4 contains statistical tables of the OECD Secretariat.
Includes bibliographic footnotes.
usc 15/08/18
Loans
Keywords: Economic assistance; Technical assistance; Developing countries